Determination of QRIS Usage Interest by Generation Z: The Influence of Perceived Ease, Benefits, Security, and Social Influence in Yogyakarta Province - Chandra Putry, Nur Anita; Tohir, Anida (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the influence of perceived ease of use, benefits, security, and social influence on the interest in using the Indonesian Standard Quick Response Code (QRIS) among Generation Z in Yogyakarta Province. With a compatible digital payment system, QRIS has great potential among Generation Z who are familiar with technology. The method in this study was quantitative by distributing questionnaires to 150 people from Generation Z in Yogyakarta Province. Data were analyzed using multiple linear regression. The results of this study indicate that perceived ease of use does not have a significant negative effect on interest in using QRIS. Meanwhile, perceived benefits, security, and social influence have a significant positive effect. These findings indicate that success in QRIS adoption is not only determined by technical ease, but also by tangible benefits, a sense of security, and the social environment of the user. These results have a significant impact on efforts to develop more efficient methods for offering and teaching QRIS to the Generation Z group.